Bifunctional metal oxides and their use in paraffin isomerization

JP2024523886A5Active Publication Date: 2025-03-18EXXONMOBIL TECHNOLOGY & ENGINEERING CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023577523
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-06-17
Filing Date
2022-06-08
Publication Date
2025-03-18
Estimated Expiration
2042-06-08

AI Technical Summary

Technical Problem

Conventional paraffin isomerization processes struggle to efficiently convert C7+ normal paraffins to branched alkanes due to excessive cracking, leading to lower yields of branched paraffins and reduced octane numbers, particularly in shale oil naphtha, which is rich in unbranched and monobranched paraffins.

Method used

The use of mixed metal oxides, comprising tungsten, zirconium, and variable oxidation state metals like Fe, Mn, Co, Cu, or Ce, with specific compositions and surface areas, reduces cracking and enhances isomerization of C7+ paraffins by promoting isomerization under controlled conditions.

Benefits of technology

The mixed metal oxides effectively isomerize C7+ paraffins with reduced cracking, increasing the octane number of hydrocarbon resources and producing branched alkanes suitable for gasoline and diesel components, while maintaining high surface area and acidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000031_0000
    Figure 00000031_0000
  • Figure 00000031_0001
    Figure 00000031_0001
  • Figure 00000032_0000
    Figure 00000032_0000
Patent Text Reader

Abstract

The zirconium tungstate catalyst for paraffin isomerization may be at least partially crystalline and comprise a mixed metal oxide comprising tungsten, zirconium, and a variable oxidation state metal selected from Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof. The mixed metal oxide comprises about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to 5% by weight of a variable oxidation state metal, each based on the total weight of the mixed metal oxide. The mixed metal oxide has a crystallinity of about 50 m, as measured according to ISO 9277. 2 / g or greater total surface area, and at least one of the following: an ammonia uptake of about 0.05 to about 0.3 mmol / g, as measured by temperature programmed adsorption / desorption, or a collidine uptake of about 100 μmol / g or greater, as measured gravimetrically.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Application No. 17 / 349986, filed June 17, 2021, which is incorporated by reference herein in its entirety.

[0002] FIELD OF THEINVENTION The present disclosure relates to paraffin isomerization. [Background technology]

[0003] Isomerization of linear and monobranched paraffins (alkanes) to form more highly branched paraffins is frequently performed to improve octane number. Isomerization of paraffins to form more highly branched alkanes can be achieved using bifunctional catalysts such as mixed metal oxides. Without being bound by theory or mechanism, it is believed that such catalysts promote paraffin isomerization through dehydrogenation, protonation to form carbenium ions, and skeletal rearrangements of the carbenium ions, such as mechanisms involving cyclopropyl cations.

[0004] In a conventional paraffin isomerization process, a paraffin feed mixture is heated in the presence of hydrogen and a suitable bifunctional catalyst. U.S. Patent Application Publication No. 2013 / 0324782 describes an example of a conventional paraffin isomerization process utilizing a bifunctional catalyst. U.S. Patent Nos. 6,080,904 and 6,124,232 provide further details of bifunctional catalysts that are acidic metal oxide catalysts and paraffin isomerization processes carried out therewith. 5 and C 6 Normal paraffins can easily undergo isomerization in such processes. For example, catalysts such as chlorinated alumina, sulfated zirconia, and zeolites are highly selective for cracking and produce C. 5 and C 6 It can be used to isomerize paraffins. In contrast, C 7+Normal paraffins become increasingly susceptible to cracking under isomerization reaction conditions, especially at high reaction temperatures and feed mixture conversions, even in the presence of zirconium tungstate catalysts that are less prone to cracking. Excessive cracking leads to lower yields of the desired branched paraffins and lower octane numbers. Without being bound by theory or mechanism, it is believed that cracking occurs by beta-scission of cationic intermediates. During beta-scission, C 5 and C 6 Normal paraffins induce the formation of the ethyl cation, a primary carbenium ion that is difficult to form. 7+ Paraffins are more stable and can more easily generate secondary or tertiary carbenium ions by β-scission. Therefore, under the isomerization reaction conditions, C 7+ Paraffin cracking can be difficult to mitigate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Application Publication No. 2013 / 0324782 [Patent Document 2] U.S. Patent No. 6,080,904 [Patent Document 3] U.S. Patent No. 6,124,232 Summary of the Invention [Problem to be solved by the invention]

[0006] U.S. shale oil production is growing rapidly. Unfortunately, shale oil is typically rich in naphtha hydrocarbons with limited branching, low octane numbers, and short ignition delays that make it prone to engine knocking and may be undesirable for incorporation into fuel blends without further processing. Branched hydrocarbons with higher octane numbers are typically desirable as blending components for the production of premium gasoline. Conventional isomerization processes are not particularly efficient at increasing the octane number of shale oil naphthas. This is due to the fact that C 7 and C 8 This is because normal paraffins are the main component of this hydrocarbon resource and tend to undergo extensive cracking instead. Catalytic reforming is also not a particularly desirable option for processing shale oil naphtha due to the rather low energy efficiency of such a process and the often low starting aromatics content of this hydrocarbon resource. Catalytic reforming is the most efficient method for the C 8+ While potentially viable for some components, this approach still leaves a significant portion of the as-produced hydrocarbon resource without an efficient conversion route to form branched paraffins with high octane numbers. [Means for solving the problem]

[0007] Summary of the Invention In some embodiments, the present disclosure provides a composition comprising a mixed metal oxide, the composition being at least partially crystalline and comprising a mixed metal oxide comprising tungsten, zirconium and a variable oxidation state metal, the variable oxidation state metal comprising a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof, the mixed metal oxide comprising about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to about 5% by weight of the variable oxidation state metal, each based on the total weight of the mixed metal oxide, the mixed metal oxide having an average particle size of about 50 μm as measured according to ISO 9277. 2 / g or greater total surface area, and at least one of the following: ammonia uptake of about 0.05 to about 0.3 mmol / g, as measured by temperature programmed adsorption / desorption, or collidine uptake of about 100 μmol / g or greater, as measured gravimetrically.

[0008] In some or other aspects, the present disclosure provides a method of forming a mixed metal oxide, the method comprising combining in a reaction mixture under alkaline conditions having a pH of about 7.5 or greater a zirconium source, a tungsten source, and a variable oxidation state metal source, obtaining a slurry comprising a co-precipitation reaction product formed from the zirconium source, the tungsten source, and the variable oxidation state metal source under alkaline conditions, digesting the slurry to obtain an amorphous digestion product from the co-precipitation reaction product. and calcining the amorphous digestion product in air at a temperature in the range of about 700° C. to about 900° C. to obtain a mixed metal oxide, wherein the variable oxidation state metal comprises a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof, the mixed metal oxide being at least partially crystalline and comprising about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to about 5% by weight variable oxidation state metal, each based on a total weight of the mixed metal oxide, the mixed metal oxide having a crystallinity of about 50 m as measured in accordance with ISO 9277. 2 / g or greater total surface area and at least one of the following: an ammonia uptake of about 0.05 to about 0.3 mmol / g, as measured by temperature programmed adsorption / desorption, or a collidine uptake of about 100 μmol / g or greater, as measured gravimetrically.

[0009] In yet another aspect, the present disclosure provides a method for isomerizing normal paraffins, the method comprising heating a mixed metal oxide under hydrogen to form an activated catalyst, contacting the activated catalyst with a hydrocarbon feed under isomerization reaction conditions, and reacting at least one C 7+and forming one or more branched alkanes from the normal alkanes, wherein the mixed metal oxide is at least partially crystalline and comprises about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to about 5% by weight of a variable oxidation state metal, the mixed metal oxide being further impregnated with about 0.01% to about 2% by weight of a precious metal, each based on the combined weight of the mixed metal oxide and the precious metal, and the mixed metal oxide has a molecular weight of about 50 m as measured in accordance with ISO 9277. 2 / g or more total surface area, and at least one of the following: ammonia uptake of about 0.05 to about 0.3 mmol / g, as measured by temperature programmed adsorption / desorption, or collidine uptake of about 100 μmol / g or more, as measured gravimetrically, and said hydrocarbon feedstock is at least one C 7+ Contains normal alkanes. [Brief description of the drawings]

[0010] BRIEF DESCRIPTION OF THE DRAWINGS The following figures are included to illustrate certain aspects of the present disclosure and should not be considered as exclusive embodiments. The disclosed subject matter is capable of considerable modification, permutations, combinations, and equivalents in form and function, as will occur to those skilled in the art having the benefit of this disclosure.

[0011] [Figure 1] FIG. 1 is a graph showing the powder XRD profiles of the samples produced in Examples 5-8 and their corresponding surface areas.

[0012] [Figure 2A] FIG. 2A is a graph showing the powder XRD profiles and corresponding surface areas of the sample produced in Example 1 at various stages of the process. [Figure 2B] FIG. 2B is a graph showing the powder XRD profiles and corresponding surface areas of the samples produced in Example 5 at various stages of the process.

[0013] [Diagram 3] FIG. 3 is a graph showing the powder XRD profiles of the mixed metal oxide of Example 5 calcined at three different temperatures.

[0014] [Figure 4] FIG. 4 is a graph showing the distribution of surface acidity as a function of calcination temperature for the mixed metal oxide of Example 5.

[0015] [Diagram 5] FIG. 5 is a graph of the ratio of n-heptane conversion: cracking rate as a function of cracking rate for the mixed metal oxide of Example 5 at a temperature of 160° C., 200 psig, and a H2:n-heptane ratio of 2:1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Detailed Description of the Invention The present disclosure relates to the isomerization of paraffins, and more specifically to the isomerization of C 7+ The present invention relates to compositions comprising mixed metal oxides that can promote the isomerization of paraffins under conditions that result in reduced cracking selectivity for normal paraffins. The compositions and methods disclosed herein are directed to the use of C2O3, which may be subject to excessive cracking under isomerization reaction conditions. 7+ It may be particularly suitable for promoting the isomerization of naphtha feedstocks containing paraffins.

[0017] As mentioned above, normal paraffins can be isomerized to increase the octane number, but 7+ Excessive cracking of normal paraffins can be problematic in a number of ways. 7+ To counter the thermodynamic advantage of cracking normal paraffins, isomerization may be performed at lower temperatures and lower feed mixture conversions, which may be undesirable from a process efficiency standpoint. For example, hydrocarbon resources rich in normal paraffins, such as naphtha, especially C 7+It can be difficult to improve the octane number of hydrocarbon resources that are rich in unbranched and monobranched paraffins.

[0018] Bifunctional metal oxides (mixed metal oxides) comprising an acidic solid oxide of a Group 4 metal, preferably Ti or Zr, modified with an anion or oxyanion of a Group 6 metal, preferably Mo or W, are represented by the formula C 7+ Although the degree of cracking of normal paraffins may still remain undesirably high, it may be particularly effective for promoting paraffin isomerization with limited cracking. Conventional zirconium tungstate catalysts are representative examples. Optionally, a variable oxidation state metal, preferably a first-row transition metal or Ce, may be present in the zirconium tungstate catalyst. Transition metals include metals from groups 3 to 12 of the periodic table. Particularly suitable variable oxidation state metals include Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof. The variable oxidation state metal may be Fe in a particular example. Optionally, a first-row transition metal that does not have a variable oxidation state may be present. Bifunctional metal oxides that are mixed metal oxides may be prepared by co-precipitation, calcination, and extrusion to form catalyst particles of suitable shape. The bifunctional metal oxide may be further impregnated with a Group 8 or 9 metal or Group 10 metal (noble metal), preferably Pt or Pd, such as by incipient wetness or vacuum infiltration.

[0019] The present disclosure provides mixed metal oxides, particularly zirconium tungstate oxides, that have different compositions and functional performances than conventional isomerization catalysts, as well as methods for preparing such mixed metal oxides. Surprisingly, small changes in the morphology and composition of the mixed metal oxides can significantly reduce the extent of cracking under isomerization reaction conditions. This effect is believed to be related to surface area. Accordingly, the present disclosure includes mixed metal oxides that are at least partially crystalline and include tungsten, zirconium, and a variable oxidation state metal, the variable oxidation state metal including a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof. The mixed metal oxides each comprise about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to about 5% by weight of the variable oxidation state metal, based on the total mass of the mixed metal oxide. The mixed metal oxides have a surface area of ​​about 50 m as measured by nitrogen BET adsorption / desorption isotherms as provided in ISO 9277. 2 / g or more total surface area. Further details of BET adsorption / desorption isotherm measurements are provided in Journal of the American Chemical Society, 1938, 60(2), pp. 309-319. The mixed metal oxides also exhibit at least one of an ammonia uptake measured by temperature programmed adsorption / desorption of about 0.05 to about 0.3 mmol / g or a collidine uptake of about 100 μmol / g or more, as described in: Applied Catalysis A: General, 1997, 165, 57-72. Collidine uptake may be measured gravimetrically under the same temperature and pressure conditions as ammonia uptake, without measuring desorption. Ammonia uptake measured by temperature programmed adsorption / desorption may be a preferred characterization method. Such bifunctional metal oxides are capable of cracking paraffins, especially C, with reduced extent of cracking, especially compared to conventional zirconium tungstate catalysts. 7+ It can be effective in promoting the isomerization of normal paraffins and monobranched paraffins.

[0020] The present disclosure further provides a method for producing the above composition, comprising: mixing a zirconium source, a tungsten source, and a variable oxidation state metal source in a reaction mixture under alkaline conditions having a pH of about 7.5 or greater; obtaining a slurry containing a co-precipitation reaction product formed from the zirconium source, the tungsten source, and the variable oxidation state metal source under alkaline conditions; digesting the slurry at a digestion temperature to form an amorphous digestion product from the co-precipitation reaction product; and calcining the amorphous digestion product in air at a temperature ranging from about 700° C. to about 900° C. to obtain a mixed metal oxide, wherein the variable oxidation state metal source comprises a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof, and the mixed metal oxide is at least partially crystalline and comprises about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to about 5% by weight variable oxidation state metal, respectively, based on the total mass of the mixed metal oxide. Mixed metal oxides are approximately 50m 2 / g or greater total surface area, and at least one of the following: ammonia incorporation of about 0.05 to about 0.3 mmol / g, or collidine incorporation of about 100 μmol / g or greater. The conditions for measuring these values ​​are specified above. Here, the reaction mixture may be formed by mixing a first solution containing a tungsten source with a second solution containing a zirconium source and a variable oxidation state metal source in an alkaline solution having a pH of about 9 to about 10.

[0021] Additionally, the reaction mixture may be formed to promote co-precipitation in an alkaline solution, such as, for example, in the presence of ammonium hydroxide or alkylammonium hydroxide. A hydroxide precipitate may first be formed from a group 4 salt (e.g., an acidic solution of Zr) and an anion or oxyanion containing a group 6 metal (e.g., a basic solution of W). The hydroxide precipitate may be amorphous and have a very large surface area. The hydroxide precipitate may then be converted to a mixed metal oxide by calcination, but the surface area after calcination is significantly smaller. Calcination may be performed in air at a temperature of, for example, about 600°C to about 900°C, or about 650°C to about 850°C, or about 700°C to about 800°C.

[0022] The present disclosure relates to a method for producing a zeolite-based zeolite having a surface area of ​​1000 nm, a zeolite-based ... 7+ While suppressing the cracking of normal paraffins and monobranched paraffins, e.g., C 5 ~C 7 C-like isomerization of alkanes 5 ~C 30 It is advantageously demonstrated that it is possible to increase the isomerization of alkanes. 5 ~C 7 C like range 5 ~C 30 In addition to inhibiting paraffin cracking in the range of C 8 ~C 30 range or C 10 ~C 30 This may facilitate reduced cracking when isomerizing larger paraffins of 100 to 200 MPa. Hydrocarbons within this size range may be useful as diesel components or lubricants, and it may be beneficial to isomerize to reduce melting points, modify pour points, cloud points, or viscosity index as needed for specific end use applications. Thus, the present disclosure offers broad applicability beyond just increasing the octane number of gasoline hydrocarbons.

[0023] All numerical values ​​within the detailed description and claims of this specification are modified by "about" or "approximately" with respect to the indicated value to take into account experimental error and variations that would be expected by one of ordinary skill in the art. Unless otherwise stated, ambient temperature (room temperature) is about 25°C.

[0024] As used in this disclosure and claims, the singular forms "a," "an," and "the" include the plural forms unless the context clearly dictates otherwise.

[0025] As used herein, the term "and" as used in phrases such as "A and / or B" is intended to include "A and B," "A or B," "A" and "B."

[0026] For the purposes of this disclosure, a new numbering scheme for the Groups of the Periodic Table is used. In the above numbering scheme, the Groups (columns) are numbered consecutively from left to right from 1 to 18.

[0027] As used herein, the term "hydrocarbon" refers to (i) any compound consisting of hydrogen and carbon atoms, or (ii) any mixture of two or more such compounds in (i). n The term "hydrocarbon" means (i) any hydrocarbon compound containing carbon atoms in its molecular structure having a total number of n carbon atoms, where n is a positive integer, or (ii) any mixture of two or more such hydrocarbon compounds. n Hydrocarbons can have any degree of unsaturation. 2 Hydrocarbon may refer to ethane, ethylene, acetylene, or a mixture of at least two of these hydrocarbons in any proportion. n+The term "hydrocarbon" means (i) any hydrocarbon compound containing n or more carbon atoms in its molecular structure, or (ii) any mixture of two or more such hydrocarbon compounds in (i). n- The term "hydrocarbon" means (i) any hydrocarbon compound containing n or fewer carbon atoms in its molecular structure, or (ii) any mixture of two or more such hydrocarbon compounds in (i).

[0028] As used herein, the term "naphtha" refers to 4 ~C 12 Hydrocarbons, especially C 4 ~C 12 It refers to saturated hydrocarbons.

[0029] As used herein, the terms “paraffin”, “alkane”, and “saturated hydrocarbon” are synonymous with each other and are represented by the formula C n H 2n+2 The term "hydrocarbon" refers to a hydrocarbon having the following structure:

[0030] As used herein, the terms "linear" and "normal" are synonymous and refer to a hydrocarbon with no side chain branching.

[0031] As used herein, the term "cracking" refers to the conversion of a given hydrocarbon molecule into two smaller hydrocarbon molecules.

[0032] As used herein, the term "isomerization" refers to rearrangement of the hydrocarbon backbone, specifically the conversion of normal paraffins to branched paraffins.

[0033] As used herein, the term "weight hour space velocity" (WHSV) refers to a measure of the weight of feed mixture flowing per unit weight of catalyst per hour.

[0034] As used herein, the term "liquid hour space velocity" (LHSV) refers to a measure of the volume of feed mixture flowing per unit volume of catalyst per hour.

[0035] As used herein, the term "variable oxidation state metal" refers to a metal that has two or more available oxidation states other than the zero oxidation state.

[0036] As used herein, the term "total surface area" refers to the total surface area of ​​a material that is physically adsorbed N2O3, as specified, for example, in ISO 9277. 2 The sum of the external and internal specific surface areas of a dispersed or porous solid (microporous material) as determined by measuring the amount of adsorption / desorption isotherm.

[0037] As used herein, the term "ammonia uptake" refers to the measurement of temperature programmed ammonia adsorption / desorption of a dispersed or porous solid (microporous material), as measured as described in Applied Catalysis A: General, 1997, 165, 57-72.

[0038] As used herein, the term "collidine uptake" refers to the millimoles of collidine (a catalyst poison) absorbed per gram of sample. In a non-limiting example, a sample may be dried under a nitrogen stream at 200° C. for 60 minutes on a thermogravimetric analyzer (Model Q5000, TA Instruments, New Castle, Del.) before exposing the sample to collidine and measuring the gravimetric amount of collidine adsorbed.

[0039] As used herein, the term "digestion" refers to a thermal treatment performed by heating a solid in a solvent in which impurity species are soluble but the bulk of the solid is not. Digestion may result in species equilibration along with digestion of particles of the insoluble solid. The digestion conditions, including digestion temperature, may affect the surface area and porosity of the resulting mesoporous material.

[0040] Composition and method for producing same The composition of the present disclosure may comprise an acidic solid oxide (mixed metal oxide) of a Group 4 metal, preferably Ti or Zr, modified with an anion or oxyanion of a Group 6 metal, preferably Mo or W. Optionally, a variable oxidation state metal may be present, the variable oxidation state metal comprising a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof. The composition may be prepared by co-precipitation, calcination and extrusion to form catalyst particles of suitable shape. The extrudates may be prepared in the presence of a binder or in the absence of a binder. The composition may be further impregnated with a Group 8 or 9 metal or a Group 10 metal (noble metal), preferably Pt or Pd, for example, by incipient wetness or vacuum infiltration. The incorporation of a noble metal may promote catalytic activity for paraffin isomerization.

[0041] In a more specific example, the mixed metal oxide can be impregnated with a precious metal, and the precious metal is present in an amount of about 0.01% to about 2% by weight, or about 0.05% to about 1.8% by weight, or about 0.1% to about 1.6% by weight, or about 0.2% to about 1.4% by weight, or about 0.3% to about 1.2% by weight, or about 0.4% to about 1% by weight, based on the total weight of the mixed metal oxide and the precious metal. The precious metal can include at least one precious metal selected from the group consisting of Pt, Pd, Rh, and any combination thereof. Preferably, the precious metal includes Pt.

[0042] The mixed metal oxides of the present disclosure may include Zr as the Group 4 metal and W as the Group 6 metal. Such mixed metal oxides may be referred to herein as zirconium tungstate oxide catalysts or zirconium tungstate catalysts, and include about 5% to about 25% by weight W, about 40% to about 70% by weight Zr, and about 0.01% to about 5% by weight of a variable oxidation state metal, preferably Fe, based on the total mass of the mixed metal oxide. In some cases, the mixed oxides include about 9% to about 20% by weight W, about 40% to about 70% by weight Zr, and about 0.01% to about 2% by weight of a variable oxidation state metal, based on the total mass of the mixed metal oxide. Preferably, the mixed metal oxides include about 0.5% to 0.7% by weight of a variable oxidation state metal, based on the total mass of the mixed metal oxide.

[0043] The variable oxidation state metal may be selected from the group consisting of Fe, Mn, Cu, Co, Ce, Ni, and any combination thereof. In at least one embodiment, the variable oxidation state metal may include Fe.

[0044] When activated, the mixed metal oxides can be effective to isomerize n-heptane at a conversion:cracking rate ratio of about 10 or greater, or at a cracking rate of about 10% or less. 5+ C produced during isomerization of alkane feed mixtures 1 ~C 4 It can be determined by the mass of the hydrocarbon.

[0045] As used herein, the mixed metal oxide is about 75 m 2 / g or more, or about 85m 2 In a more specific example, the mixed metal oxide may have a total surface area of ​​about 50 m / g or more. 2 / g~about 150m 2 / g, or about 60m 2 / g ~ approx. 120m 2 / g, or about 70m 2 / g ~ approx. 110m 2 Such measurements may be in the range of N / g, in particular according to ISO 9277.2 This can be done by BET adsorption / desorption isotherms.

[0046] Mixed metal oxides have W atoms / nm 2 The tungsten (W) surface density may range from about 2 to about 20 (or from about 2.2 to about 18, or from about 2.4 to about 16, or from about 2.4 to about 14, or from about 2.6 to about 12, or from about 2.8 to about 10, or from about 3 to about 8, or from about 4 to about 12, or from about 5 to about 7), as measured by (a) the measured W content (wt%) obtained by X-ray fluorescence, and (b) the N 2 It can be calculated from the measured surface area obtained by the BET method.

[0047] The mixed metal oxide is monoclinic zirconium oxide (m-ZrO 2 ) to monoclinic tungsten oxide (m-WO 3 ) may have an X-ray diffraction peak height ratio in the range of 0 to about 5. 3 is synonymous with monoclinic tungsten oxide. m-ZrO 2 is synonymous with monoclinic zirconium oxide. More preferably, the X-ray diffraction peak height ratio may be in the range of 0 to 3. The X-ray diffraction peaks are expressed as 2θ values ​​and are determined using CuKα radiation. The following approximate 2θ peak positions are characteristic: m-WO 3 = 24.4° and m-ZrO 2 =28.4°. Tetragonal ZrO 2 (t-ZrO 2 ) is found at a 2θ peak position of 30.2°. m-ZrO 2 m-WO 3 A higher ratio of may be associated with less W becoming active.

[0048] The composition of the present disclosure may further comprise a binder in combination with the mixed metal oxide. Up to about 50% by weight of the binder may be present. The binder may comprise at least one material selected from the group consisting of W / Zr oxide, W / Zr hydroxide, W oxide, W hydroxide, Zr oxide, Zr hydroxide, Fe oxide, Fe hydroxide, Ti oxide, Ti hydroxide, silica, silica alumina, titania silica, aluminum oxide, aluminum hydroxide, and any combination thereof. Extruded samples may also be self-bonded (i.e., no binder is present).

[0049] When preparing the composition by coprecipitation and calcination, suitable sources of group 4 metals include, for example, group 4 salts such as chlorides, oxychlorides, nitrates, acetates, alkoxides (e.g., Zr salts). Ti and / or Y may be included in combination with Zr. Suitable sources of anions or oxyanions including group 6 metals, preferably W, include, for example, ammonium or alkali metal metatungstate (Na or K), ammonium or alkali metal metamolybdate (Na or K), tungsten chloride, molybdenum chloride, tungstate, molybdate, and any combination thereof. Suitable sources of variable oxidation state metals typically include metal salts, particularly water-soluble metal salts such as metal sulfates, nitrates, and / or acetates. When the metal is Fe, a suitable Fe source includes FeSO 4 , Fe 2 (SO 4 ) 3 , Fe(NO 3 ) 2 , Fe(NO 3 ) 3 or Fe(III) acetate or Fe(II) acetate. When the metal is Mn, suitable Mn sources include MnSO 4 , Mn(NO 3 ) 2 or Mn acetate. When the metal is Co, suitable Co sources include CoSO 4 , Co(NO 3 ) 2or Co acetate. When the metal is Cu, suitable Cu sources include CuSO 4 , Cu(NO 3 ) 2 When the metal is Ce, suitable sources of Ce include Ce 2 (SO 4 ) 3 , Ce(SO 4 ) 2 , Ce(NO 3 ) 2 , Ce(NO 3 ) 3 or Ce(III) acetate or Ce(II) acetate. When the metal is Ni, suitable Ni sources include NiSO 4 , Ni(NO 3 ) 2 , or Ni acetate.

[0050] Coprecipitation can occur in an alkaline solution, such as in the presence of ammonium hydroxide or alkylammonium hydroxide. A hydroxide precipitate can first be formed from a group 4 salt and an anion or oxyanion containing a group 6 metal. The hydroxide precipitate can be amorphous and have a large surface area. The hydroxide precipitate can then be converted to a mixed metal oxide by calcination, but the surface area after calcination is significantly smaller. Calcination can be performed in air at a temperature of, for example, about 600°C to about 900°C, or about 650°C to about 850°C, or about 700°C to about 800°C.

[0051] In at least one embodiment, after co-precipitation, the resulting powder is (a) washed with water and dried at a temperature ranging from about 110°C to 140°C (e.g., 120°C), (b) washed with an ammonium salt solution, (c) calcined at a temperature ranging from about 600°C to about 900°C, (d) molded into a desired shape, (e) washed with an ammonium salt solution, and (f) calcined at 600°C or less. A metal (e.g., a noble metal) may then be added and the metal oxidized to remove ligands and form a metal oxide. The metal may then be reduced prior to paraffin isomerization. Tungsten and other components in the composition may also undergo reduction in this process.

[0052] Prior to calcination, the hydroxide precipitate may be digested to form an amorphous digested product. Digestion may be carried out at a temperature of from about 25° C. to about 200° C., preferably from about 40° C. to about 150° C., or from about 60° C. to about 120° C. Surprisingly, the digestion temperature can have a significant effect on the surface area obtained after calcination.

[0053] The precious metal precursor may be impregnated into the mixed metal oxide following the formation of the mixed metal oxide by calcination. Suitable techniques for incorporating the precious metal precursor may include incipient wetness impregnation, vacuum infiltration impregnation, or any combination thereof. The precious metal precursor may include at least one precious metal selected from the group consisting of Pt, Pd, Rh, and any combination thereof. In the case of Pt, the precious metal precursor may be, for example, (NH 3 ) 2 H 2 PtCl 4 Mixed ligands (or ligands) such as (NH 3 ) 4 Pt(NO 3 ) 2 , (NH 3 ) 4 Pt(OH) 2 , (NH 3 ) 4 PtCl 2 , H 2 PtCl 6 The metal complexes may include water-soluble metal complexes selected from the group consisting of: , , and any combination thereof. Other mixed ligand complexes may also be suitable.

[0054] Once formed by calcination, the mixed metal oxide may be impregnated with a precious metal such as a group 8-10 metal, preferably Pt or Pd (via a suitable precious metal precursor), or may be first extruded to form the mixed metal oxide into a suitable shape, such as, for example, pellets, cylinders, lobes, etc. Extrusion may be performed in possible shapes and sizes, such as, for example, 1 / 10 inch cylinders, 1 / 8 inch cylinders, quadruple lobes, and trilobes, 1 / 16 inch cylinders, quadruple lobes, and trilobes, and 1 / 20 inch cylinders, quadruple lobes, and trilobes. Extrusion may be performed in the presence of extrusion aids, such as, for example, cellulose, methylcellulose, hydrogenated or ethoxylated oils (e.g., vegetable, coconut, soy, or palm), and / or polymers (e.g., PVA). Optionally, the mixed metal oxide may be mixed with a binder, such as, for example, silica, alumina, or other suitable binders, prior to extrusion. In some examples, the extrusion of the calcined powder may be carried out using oxides or hydroxides of silica, titania, lanthana, yttria, zirconia, tungsten, iron, tungsten / zirconia, and mixtures thereof as binders. Thus, the method of the present disclosure may further comprise forming an extrudate from the mixed metal oxide, optionally co-extruding the mixed metal oxide with a binder to form the extrudate. A typical composition range for extrusion is about 0:100-50:50, preferably about 0:100-35:65 or about 0:100-25:75 binder:mixed metal oxide by weight. Following extrusion, calcination may be carried out again, for example at a temperature of about 600° C. or less.

[0055] In at least one embodiment, extrusion can be accomplished by either (a) forming a dry powder of the mixed metal oxide and calcining the dry powder at a temperature in the range of about 600° C. to about 900° C. to form the active phase, or (b) first calcining the powder to form the active phase, and forming and calcining at a temperature of about 600° C. or less.

[0056] Once the mixed metal oxide is formed, optionally following extrusion, it may be impregnated with a metal suitable for promoting isomerization in the presence of hydrogen gas, particularly through a dehydrogenation / hydrogenation mechanism. Groups 8-10 metals may be effective in this regard. Impregnation may be performed, for example, using incipient wetness or vacuum infiltration. Preferably, the metal suitable for promoting isomerization may be a noble metal, such as, for example, Pt or Pd. In the case of Pt, suitable sources for introducing this metal may include, for example, chloroplatinic acid, tetraammine platinum complexes, platinous chloride, and any combination thereof. After impregnation of the mixed metal oxide has been performed, the metal suitable for promoting isomerization may likewise be converted to the oxide form of the metal by calcination, for example, at a temperature ranging from about 280° C. to about 360° C.

[0057] Isomerization method Further, the method of the present disclosure includes heating the mixed metal oxide under hydrogen to form an activated catalyst, and 7+ and contacting the activated catalyst with a hydrocarbon feed under isomerization reaction conditions, wherein the mixed metal oxide is at least partially crystalline and comprises about 5 wt.% to about 25 wt.% tungsten, about 40 wt.% to about 70 wt.% zirconium, and about 0.01 wt.% to about 5 wt.% variable oxidation state metal, the mixed metal oxide being further impregnated with about 0.01 wt.% to about 2 wt.% precious metal, based on the total weight of the mixed metal oxide and the precious metal, respectively, and the mixed metal oxide is at least about 50 m. 2 / g or more, and at least one of the following: ammonia incorporation of about 0.05 to about 0.3 mmol / g, or collidine incorporation of about 100 μmol / g, and the hydrocarbon feedstock has at least one C 7+ The hydrocarbon feedstock contains at least one C 7+ Contains normal alkanes.

[0058] In at least one embodiment, the activated catalyst is a bifunctional metal oxide catalyst (mixed metal oxide catalyst) effective for promoting the isomerization of normal paraffins, for example, as defined by the described compositions. Mixed metal oxides may be impregnated with a noble metal to form a suitable bifunctional metal oxide catalyst.

[0059] The hydrocarbon feedstock may be, for example, C 5 ~C 7 Normal paraffin, or C 7+ Normal paraffins and / or monobranched paraffins of at least C 5 ~C 30 The hydrocarbon feedstock may also include normal paraffins of, for example, C 8 ~C 30 C like normal paraffin 7+ Normal paraffins and monobranched paraffins (e.g., C 5 Monobranched paraffin, C 6 Monobranched paraffin or C 7+ Monobranched paraffin), C 5 Normal paraffin, C 6 Specific hydrocarbon feedstocks suitable for use in the present disclosure may include normal or mono-branched C 5 Paraffin, normal or monobranched C 6 Paraffin and normal or monobranched C 7 Optionally, at least some normal or monobranched C 8 Paraffins may also be present in such hydrocarbon feedstocks. Other suitable hydrocarbon feedstocks for use in the present disclosure include C 10 It may comprise normal paraffins or monobranched paraffins. Any of the foregoing may further comprise one or more aromatic compounds.

[0060] Optionally, one or more naphthenic compounds may be combined with any of the aforementioned hydrocarbon feedstocks. Co-feeding one or more naphthenic compounds may further reduce the incidence of cracking. About 10 wt. % or more naphthenic compounds may be present in combination with the hydrocarbon feedstock. Suitable naphthenic compounds may include, for example, branched naphthenic compounds such as methylcyclopentane (MCP), methylcyclohexane (MCH), or any combination thereof. Other suitable branched naphthenic compounds may also be suitable for use in the present disclosure, such as, for example, ethylcyclopentane, propylcyclopentane, 1,1-dimethylcyclopentane, 1,1-dimethylcyclohexane, ethylcyclohexane, propylcyclohexane. Bicyclic naphthenic compounds may be suitable as well. In general, any naphthenic compound capable of forming a tertiary carbenium ion under isomerization reaction conditions may be effectively used in the present disclosure.

[0061] The activated catalyst may be contacted with the hydrocarbon feedstock under one or more of the following isomerization reaction conditions: a temperature in the range of about 150° C. to about 210° C., preferably in the range of about 150° C. to about 190° C.; a molar ratio of hydrogen to hydrocarbon feedstock in the range of about 1:1 to about 3:1; a pressure in the range of about 100 psig to about 350 psig; and a reaction time of about 0.5 h. -1 ~about 6h -1 The liquid hourly space velocity may range from about 50 kPa to about 2000 kPa. In a particular example, the isomerization reaction conditions are from about 6 h -1 Less than or equal to 5 hours -1 Less than or equal to 4 hours -1 Liquid hourly space velocity of less than or equal to about 2hr -1 ~About 5 hours -1 The LHSV may range from 0 to 100 .

[0062] Regarding the conditions for the isomerization reaction, the isomerization reaction can be carried out in a gas phase, a supercritical phase, or a liquid phase.

[0063] The isomerization reaction conditions are 5 ~C 7The conversion of normal paraffins may be about 95% or less, or about 90% or less, or about 85% or less, or about 80% or less, or about 75% or less, or about 70% or less. 5 ~C 7 or C 7+ Normal paraffins may be converted at about 70% to about 90%. The cracking rate of n-heptane may be about 10% by weight or less, and the ratio of n-heptane conversion to cracking rate may be about 10 or more, for example, about 10 to about 25, or about 10 to about 20.

[0064] Embodiments disclosed herein include the following:

[0065] A. Mixed Metal Oxide Compositions The compositions are at least partially crystalline and comprise a mixed metal oxide comprising tungsten, zirconium, and a variable oxidation state metal, the variable oxidation state metal comprising a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, and Ni, the mixed metal oxide comprising about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to about 5% by weight of the variable oxidation state metal, each based on the total weight of the mixed metal oxide, the mixed metal oxide having a crystallinity of about 50 m, as measured in accordance with ISO 9277. 2 / g or greater total surface area and at least one of the following: an ammonia uptake of about 0.05 to about 0.3 mmol / g, as measured by temperature programmed adsorption / desorption, or a collidine uptake of about 100 μmol / g or greater, as measured gravimetrically.

[0066] B. Methods for Making Mixed Metal Oxide Compositions The method comprises mixing a zirconium source, a tungsten source, and a variable oxidation state metal source in a reaction mixture under alkaline conditions having a pH of about 7.5 or greater; obtaining a slurry comprising a co-precipitation reaction product formed from the zirconium source, the tungsten source, and the variable oxidation state metal source under alkaline conditions; digesting the slurry to form an amorphous digestion product from the co-precipitation reaction product; and calcining the amorphous digestion product at a temperature in the range of about 700° C. to about 900° C. in air to obtain a mixed metal oxide, wherein the variable oxidation state metal comprises a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, and Ni, the mixed metal oxide being at least partially crystalline and comprising about 5% by weight, about 25% by weight, about 40% by weight to about 70% by weight, and about 0.01% by weight to about 5% by weight, based on a total weight of the mixed metal oxide, the mixed metal oxide having a crystallinity of about 50 m as measured in accordance with ISO 9277. 2 / g or greater total surface area and at least one of the following: an ammonia uptake of about 0.05 to about 0.3 mmol / g, as measured by temperature programmed adsorption / desorption, or a collidine uptake of about 100 μmol / g or greater, as measured gravimetrically.

[0067] C. Method for Producing Branched Alkanes The method includes heating a mixed metal oxide under hydrogen to form an activated catalyst, contacting the activated catalyst with a hydrocarbon feed under isomerization reaction conditions, and producing at least one C 7+ and forming one or more branched alkanes from the normal alkanes, the mixed metal oxide being at least partially crystalline and comprising about 5% to about 25% by weight tungsten, about 40% to about 70% by weight zirconium, and about 0.01% to about 5% by weight of a variable oxidation state metal, the mixed metal oxide being further impregnated with about 0.01% to about 2% by weight of a precious metal, based on the total weight of the mixed metal oxide and the precious metal, respectively, and the mixed metal oxide has a molecular weight of about 50 m, as measured in accordance with ISO 9277. 2 / g or more, and at least one of the following: ammonia uptake of about 0.05 to about 0.3 mmol / g, or collidine uptake of about 100 μmol / g or more, as measured by temperature programmed adsorption / desorption; and the hydrocarbon feedstock is at least one C 7+ Contains normal alkanes.

[0068] Embodiments A, B, and C may have one or more of the following elements in any combination.

[0069] Element 1: The mixed metal oxide is impregnated with a precious metal, and the precious metal is present in an amount of about 0.01% to about 2% by weight, based on the total weight of the mixed metal oxide and the precious metal.

[0070] Element 2: The precious metal comprises at least one precious metal selected from the group consisting of Pt, Pd, Rh, and any combination thereof.

[0071] Element 3: The mixed metal oxide, when activated, is effective in isomerizing n-heptane at a conversion:cracking rate ratio of about 10 or greater with a cracking rate of about 10% or less.

[0072] Element 4: The mixed metal oxide, when activated, is effective in isomerizing n-heptane at a conversion:cracking rate ratio of about 10 to about 15 at cracking rates of about 10% or less.

[0073] Element 5: Mixed metal oxides are about 60 m 2 / g ~ approx. 130m 2 / g range of total surface area.

[0074] Element 6: Mixed metal oxides have W atoms / nm 2 The tungsten surface density, as measured by the tungsten surface roughness index, ranges from about 2 to about 20.

[0075] Element 7: Mixed metal oxides include monoclinic zirconium oxide (m-ZrO 2 ) to monoclinic tungsten oxide (m-WO 3) in the range of 0 to about 5.

[0076] Element 8: The mixed metal oxide comprises about 9 wt.% to about 20 wt.% tungsten, about 40 wt.% to 70 wt.% Zr, and about 0.01 wt.% to 2 wt.% variable oxidation state metals, each based on the total weight of the mixed metal oxide.

[0077] Element 9: The mixed metal oxide comprises about 0.5% to 0.7% by weight of a variable oxidation state metal, based on the total weight of the mixed metal oxide.

[0078] Element 10: The variable oxidation state metal is selected from the group consisting of Fe, Mn, Cu, Ce, and any combination thereof.

[0079] Element 11: Variable oxidation state metals include Fe.

[0080] Element 12: The composition further comprises a binder in combination with the mixed metal oxide.

[0081] Element 13: The reaction mixture is formed by mixing a first solution containing a tungsten source, more specifically a tungsten source selected from ammonium metatungstate, alkali metal metatungstate, tungsten chloride, tungstic acid, and combinations thereof, with a second solution containing a zirconium source, particularly a zirconium salt, more specifically a zirconium source selected from zirconium chloride, zirconium oxychloride, zirconium nitrate, zirconium acetate and / or an alkoxide, and a variable oxidation state metal source, particularly a water-soluble metal salt thereof, more specifically a variable oxidation state metal source selected from sulfates, nitrates, and / or acetates of the corresponding metals in an alkaline solution having a pH of about 9 to about 10.

[0082] Element 14: The method further comprises, after calcination, introducing a precious metal precursor into the mixed metal oxide by incipient wetness impregnation, vacuum infiltration impregnation, or any combination thereof.

[0083] Element 15: Precious metal precursors are (NH 3 ) 4 Pt(NO 3 ) 2 , (NH 3 ) 4 Pt(OH) 2 , (NH 3 ) 4 PtCl 2 , H 2 PtCl 6 , (NH 3 ) 2 H 2 PtCl 4 and any combination thereof.

[0084] Element 16: Further comprising forming extrudates from the mixed metal oxide.

[0085] Element 17: Co-extruding the mixed metal oxide with a binder to form an extrudate.

[0086] Element 18: The binder comprises at least one material selected from the group consisting of W / Zr oxide, W / Zr hydroxide, W oxide, W hydroxide, Zr oxide, Zr hydroxide, Fe oxide, Fe hydroxide, Ti oxide, Ti hydroxide, silica, silica alumina, titania silica, aluminum oxide, aluminum hydroxide, and any combination thereof.

[0087] Element 19: The isomerization reaction conditions include one or more of the following: a temperature in the range of about 150° C. to about 210° C.; a hydrogen to hydrocarbon feed ratio in the range of about 1:1 to about 3:1; a pressure in the range of about 150 psig to about 350 psig; and a reaction time of about 0.5 h. -1 ~about 6h -1 Liquid hourly space velocities ranging from

[0088] As non-limiting examples, exemplary combinations applicable to A include, but are not limited to, for example, 1 or 2, and 3; 1 or 2, and 4; 1 or 2, and 5; 1 or 2, and 6; 1 or 2, and 6 and 7; 1 or 2, and 7; 1 or 2, and 8; 1 or 2, and 6-8; 1 or 2, and 7 and 8; 1 or 2, and 9; 1 or 2, and 6-9; 1 or 2, and 10; 1 or 2, and 11; 1 or 2, and 12; 1 or 2, and 4 and 5; 1 or 2, and 6; 7 and 8; 9 and 10; and 11 and 12.

[0089] As non-limiting examples, exemplary combinations applicable to B include, but are not limited to, for example, 1 or 2, and 3; 1 or 2, and 4; 1 or 2, and 5; 1 or 2, and 6; 1 or 2, and 6 and 7; 1 or 2, and 7; 1 or 2, and 8; 1 or 2, and 6-8; 1 or 2, and 7 and 8; 1 or 2, and 9; 1 or 2, and 6-9; 1 or 2, and 11; 1 or 2, and 12; 1 or 2, and 13; 1 or 2, and 14; 1 or 2, and 15; 1 or 2, and 16; 1 or 2, and 17; 1 or 2, and 18; 1 or 2, and 13 and 14; 1 or 2, and 16; 13 and 14; 13 and 15; and 13 and 16, 1 or 2, and 16, and 17, and 18.

[0090] As a non-limiting example, exemplary combinations applicable to C include, but are not limited to, for example, 1 or 2, and 3; 1 or 2, and 4; 1 or 2, and 5; 1 or 2, and 6; 1 or 2, and 6 and 7; 1 or 2, and 7; 1 or 2, and 8; 1 or 2, and 6-8; 1 or 2, and 7 and 8; 1 or 2, and 9; 1 or 2, and 6-9; 1 or 2, and 11; 1 or 2, and 12; 1 or 2, and 13; 1 or 2, and 14; 1 or 2, and 15; 1 or 2, and 16; 1 or 2, and 17; 1 or 2, and 18; 1 or 2, and 13 and 14; 1 or 2, and 16; 13 and 14; 13 and 15; and 13 and 16, 4 or 5, and 19.

[0091] To facilitate a better understanding of the present disclosure, the following examples of preferred or representative embodiments are given, which should not be construed in any way as limiting or defining the scope of the present disclosure. EXAMPLES

[0092] Working Example Example 1: Initial reagent concentrations and reaction conditions Preparation of solution A: In a beaker, add 71.7 grams of concentrated NH 4 OH and 14.9 grams (NH 4 ) 6 H 2 W 12 O 40 xH 2 Dissolve 200 ml of ammonium metatungstate (AMT) in 400 ml of H 2 Mix with stirring in 0 and heat at 60° C. Preparation of solution B: 138 grams of ZrOCl 2 xH 2 O and 2.1 g FeSO 4 400ml of H 2 In a separate vessel (where precipitation occurs), 839.4 grams of deionized water was added and NH 4The pH was adjusted to 9-10 by adding OH. The alkaline solution was then stirred at 40°C. While stirring, solutions A and B were added to the alkaline solution at 10 ml / min. After the addition of solutions A and B was complete, the resulting slurry was stirred at 40°C for 1 hour. Once the co-precipitation was complete, the slurry was transferred to another container (e.g., a polypropylene or Teflon bottle) and digested at 100°C for 72 hours. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was diluted with NH 4 NO 3 The powder may be washed with or without additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder, which consisted of an average of 0.61 wt% Fe, 15.4 wt% W, and 54.0 wt% Zr. The powder X-ray diffraction pattern (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The average peak height ratio of monoclinic tungsten oxide:monoclinic zirconium oxide from the powder X-ray diffraction was 0.55 after calcination at 750°C. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. The resulting surface area was 89 m 2 / g, NH 3 The uptake averaged 0.16 mmol / g, respectively.

[0093] Example 2: Double Reagent Concentration During Coprecipitation This example was carried out in a similar manner to Example 1, except that the scale of solutions A and B was doubled. Solutions A and B were added to an equal volume of alkaline solution for coprecipitation. Preparation of solution A: In a beaker, 143.5 grams of concentrated NH 4 OH and 29.8 grams of (NH 4 ) 6 H 2 W 12 O 40 xH 2 Dissolve 100 mL of ammonium metatungstate (AMT) in 400 mL of HO (66.9%W) 2 The mixture was stirred in O and heated at 60° C. Preparation of solution B: 276 grams of ZrOCl2 xH 2 O and 4.2 g FeSO 4 400ml of H 2 In a separate vessel (where precipitation occurs), 839.4 grams of deionized water was added and NH 4 The pH was adjusted to 9-10 with OH. The alkaline solution was stirred in a container at 40°C. While stirring, solutions A and B were added to the alkaline solution at 10 ml / min. After the addition of solutions A and B was complete, the slurry was stirred at 40°C for 1 hour. Once the co-precipitation was complete, the slurry was transferred to another container (such as a polypropylene or Teflon bottle) and digested at 100°C for 72 hours. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was dissolved in NH 4 NO 3 The powder may or may not be washed with water, followed by additional water washing and drying at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder. The powder consisted of an average of 0.65 wt% Fe, 16.4 wt% W, and 54.1 wt% Zr. The powder X-ray diffraction pattern (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The average peak height ratio of monoclinic tungsten oxide:monoclinic zirconium oxide from powder X-ray diffraction after calcination at 750°C was 0.53. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 96 m2, respectively. 2 / g, NH 3 The uptake was 0.17 mmol / g.

[0094] Example 3: Double the concentration of reagents during coprecipitation and at 25°C This example was carried out in a similar manner to Example 2, except that the coprecipitation was carried out at 23°C-25°C for 1 hour. The resulting active oxide consisted of an average of 0.51 wt% Fe, 8.9 wt% W, and 64.1 wt% Zr. The powder X-ray diffraction pattern (not shown) contained mainly tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide after calcination at 750°C was 0.44. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 93 m2, respectively. 2 / g, NH 3 The uptake was 0.19 mmol / g.

[0095] Example 4: Double Reagent Concentration During Coprecipitation, Coprecipitation at 25°C and 25°C Digestion This example was carried out similarly to Example 2, except that the coprecipitation was carried out at 23°C-25°C and the digestion was carried out at 25°C. The active oxide form of the powder consisted of an average of 0.68 wt% Fe, 15.9 wt% W, and 54.3 wt% Zr. The powder X-ray diffraction pattern (not shown) contained mainly tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The average peak height ratio from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide after calcination at 750°C was 0.60. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface area was 60 m2, respectively. 2 / g, NH 3 The uptake was 0.11 mmol / g.

[0096] Example 5: 4x Reagent Concentration During Coprecipitation This example was carried out in a similar manner to Example 1, except that it was done on a more concentrated scale in both solutions A and B and in the alkaline solution for coprecipitation. Preparation of solution A: In a beaker, add 179.4 grams of concentrated NH 4 OH and 37.3 grams of (NH 4 )6 H 2 W 12 O 40 xH 2 Dissolve 250 mL of HO (66.9% W) (ammonium metatungstate, AMT) in 250 mL of HO. 2 Mix with stirring in 0 and heat at 60° C. Preparation of solution B: 345 grams of ZrOCl 2 xH 2 O and 5.3 g FeSO 4 250ml of H 2 2. In a separate container, 525 grams of deionized water was dissolved in NH 4 The pH was adjusted to 9-10 with NH. The alkaline solution was stirred at 40°C. While stirring, solutions A and B were added to the alkaline solution at 10 ml / min. After the addition of solutions A and B was complete, the slurry was stirred at 40°C for 1 h. Once the co-precipitation was complete, the slurry was transferred to another container (e.g., a polypropylene or Teflon bottle) and digested at 100°C for 72 h. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was NH. 4 NO 3 The powder was washed with additional water and dried at 120 °C. The powder was then calcined in air at temperatures ranging from 700 °C to 850 °C to prepare the active oxide form of the powder, which consisted of an average of 0.62 wt% Fe, 16.0 wt% W, and 54.9 wt% Zr. The powder X-ray diffraction pattern (Figure 1) contained mainly tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of the average peak heights from the powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide after calcination at 750 °C was 0.90. At higher calcination temperatures (>800 °C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface area was 82 m, respectively. 2 / g, NH 3 The uptake was 0.14 mmol / g.

[0097] Example 6: 4x Reagent Concentration During Coprecipitation and Digestion in Original Vessels This example was carried out similarly to Example 5, except that after stirring at 40° C. for 1 hour, the temperature in the vessel was increased to 100° C. and the slurry was digested at 100° C. for 72 hours. After digestion, the resulting powder was filtered and washed with water. At this point, the powder contained NH 4 NO 3 The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder, which consisted of an average of 0.65 wt% Fe, 16.2 wt% W, and 54.1 wt% Zr. The powder X-ray diffraction pattern (Figure 1) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide was 1.09 after calcination at 750°C. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 87 m2 and 87 m2, respectively. 2 / g, NH 3 The uptake was 0.16 mmol / g.

[0098] Example 7: 4x Reagent Concentration During Coprecipitation and Digestion at 23-25°C This example was carried out similarly to Example 5, except that digestion was carried out at 23° C.-25° C. After digestion, the resulting powder was filtered and washed with water. At this point the powder was NH 4 NO 3The powder was washed with additional water and dried at 120 °C. The powder was then calcined in air at temperatures ranging from 700 °C to 850 °C to prepare the active oxide form of the powder, which consisted of an average of 0.71 wt% Fe, 17.1 wt% W, and 52.6 wt% Zr. The powder X-ray diffraction pattern (Figure 1) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide was 0.50 after calcination at 750 °C. At higher calcination temperatures (>800 °C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. The resulting surface areas averaged 62 m2, respectively. 2 / g, NH 3 The uptake was 0.13 mmol / g.

[0099] Example 8: 4x Reagent Concentration During Coprecipitation and Digestion at 23-25°C for 1 Hour This example was carried out similarly to Example 5, except that the digestion was carried out at 23°C-25°C for 1 hour. After digestion, the resulting powder was filtered and washed with water. After digestion, the resulting powder was filtered and washed with water. At this point, the powder contained NH 4 NO 3 The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder, which consisted, on average, of 0.72 wt% Fe, 17.4 wt% W, and 52.3 wt% Zr. The powder X-ray diffraction pattern (Figure 1) contained mainly tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide after calcination at 750°C was 1.38. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface area was 52 m2, respectively. 2 / g, NH 3 The uptake was 0.10 mmol / g.

[0100] Example 9: Four-fold reagent concentration during coprecipitation with further increased W concentration This example was carried out in a similar manner to Example 5, except that the W concentration was increased by 25%. Preparation of solution A: In a beaker, 254.6 grams of concentrated NH 4 OH and 52.9 grams of (NH 4 ) 6 H 2 W 12 O 40 xH 2 0 (66.9% W) (ammonium metatungstate, AMT) was mixed with stirring in 355 ml of HO and heated at 60° C. Preparation of solution B: 392 grams of ZrOCl 2 xH 2 O and 6.0 g FeSO 4 284ml of H 2 2. In a separate container, 525 grams of deionized water was dissolved in NH 4 The pH was adjusted to 9-10 with NH. The alkaline solution was stirred at 40°C. While stirring, solutions A and B were added to the alkaline solution at 10 ml / min. After the addition of solutions A and B was complete, the slurry was stirred at 40°C for 1 hour. Upon completion of the co-precipitation, the slurry was transferred to another container (e.g., a polypropylene or Teflon bottle) and digested at 23°C-25°C for 72 hours. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was NH. 4 NO 3The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare an active oxide form of powder, which consisted of an average of 0.60 wt% Fe, 19.2 wt% W, and 52.0 wt% Zr. Powder X-ray diffraction patterns (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide was 3.86 after calcination at 750°C. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 85 m2, respectively. 2 / g, NH 3 The uptake was 0.16 mmol / g.

[0101] Example 10: 4x reagent concentration during coprecipitation with further reduced W concentration This example was carried out in a manner similar to that of Example 5, except that the concentration of W was reduced by 25%. Preparation of solution A: In a beaker, 181.8 grams of concentrated NH 4 OH and 28.0 grams (NH 4 ) 6 H 2 W 12 O 40 xH 2 Dissolve 248 ml of HO (66.9%W) (ammonium metatungstate, AMT) in 248 ml of H 2 Mix with stirring in 0 and heat to 60° C. Preparation of solution B: 345 grams of ZrOCl 2 xH 2 O and 5.3 g FeSO 4 284ml of H 2 2. In a separate container, 525 grams of deionized water was dissolved in NH 4The pH was adjusted to 9-10 with NH. The alkaline solution was stirred at 40°C. While stirring, solutions A and B were added to the alkaline solution at 10 ml / min. After the addition of solutions A and B was complete, the slurry was stirred at 40°C for 1 hour. Upon completion of the co-precipitation, the slurry was transferred to another container (e.g., a polypropylene or Teflon bottle) and digested at 23°C-25°C for 72 hours. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was NH. 4 NO 3 The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare an active oxide form of powder, which consisted, on average, of 0.66 wt% Fe, 13.2 wt% W, and 56.0 wt% Zr. The powder X-ray diffraction pattern (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide after calcination at 750°C was 0.31. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 86 m2, respectively. 2 / g, NH 3 The uptake was 0.17 mmol / g.

[0102] Example 11: 4x Reagent Concentration during Coprecipitation with 2x Fe Concentration This example shows FeSO 4 The procedure was the same as in Example 5, except that the amount of NH was doubled (10.5 grams). After digestion, the resulting powder was filtered and washed with water. At this point, the powder was NH 4 NO 3The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder, which consisted, on average, of 1.25 wt% Fe, 16.0 wt% W, and 54.0 wt% Zr. The powder X-ray diffraction pattern (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide was 1.74 after calcination at 750°C. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 80 m2, respectively. 2 / g, NH 3 The uptake was 0.16 mmol / g.

[0103] Example 12: 4x reagent concentration during coprecipitation with 5x Fe concentration This example shows FeSO 4 The procedure was the same as in Example 5, except that the amount of NH was reduced by a factor of five (1.1 grams). After digestion, the resulting powder was filtered and washed with water. At this point, the powder was NH 4 NO 3 The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide in powder form, which consisted of an average of 0.15 wt% Fe, 16.9 wt% W, and 54.1 wt% Zr. The powder X-ray diffraction pattern (not shown) contained mainly tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. The ratio of average peak heights from powder X-ray diffraction of monoclinic tungsten oxide:monoclinic zirconium oxide after calcination at 750°C was 1.08. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 86 m2, 16.9 wt% Fe, 16.9 wt% W, and 54.1 wt% Zr, respectively. 2 / g, NH 3 The uptake was 0.16 mmol / g.

[0104] Example 13: Cu substitution for Fe under initial reagent conditions This example shows FeSO 4 Instead of 1.7 g CuSO 4 The procedure was the same as in Example 1, except that NH was used. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was 4 NO 3 The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare powders in the active oxide form, which consisted on average of 0.5 wt% Cu, 15 wt% W, and 54 wt% Zr. Powder X-ray diffraction patterns (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 91 m2, respectively. 2 / g, NH 3 The uptake was 0.17 mmol / g.

[0105] Example 14: Mn substitution for Fe under initial reagent conditions This example shows FeSO 4 Instead of 1.7 grams of MnSO 4 The procedure was the same as in Example 1, except that NH was used. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was 4 NO 3The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder, which consisted on average of 0.5 wt% Mn, 15 wt% W, and 54 wt% Zr. Powder X-ray diffraction patterns (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 88 m2, respectively. 2 / g, NH 3 The uptake was 0.18 mmol / g.

[0106] Example 15: Ce substitution for Fe in initial reagent conditions This example shows FeSO 4 Instead of 2.0 grams of Ce 2 (SO 4 ) 3 The procedure was the same as in Example 1, except that the hydrate was used. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was NH 4 NO 3 The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder, which consisted on average of 0.5 wt% Ce, 15 wt% W and 54 wt% Zr. Powder X-ray diffraction patterns (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 93 m2, respectively. 2 / g, NH 3 The uptake was 0.18 mmol / g.

[0107] Example 16: 4x Reagent Concentration During Coprecipitation Without Fe This example adds FeSO to the reaction mixture in solution B. 4The procedure was the same as in Example 5, except that no NH was included. After digestion, the resulting powder was filtered and washed with water. At this point, the powder was 4 NO 3 The powder may or may not have been washed with water. The powder was washed with additional water and dried at 120°C. The powder was then calcined in air at temperatures ranging from 700°C to 850°C to prepare the active oxide form of the powder. The powder consisted of an average of 0.02 wt% Fe, 15 wt% W, and 55 wt% Zr. Powder X-ray diffraction patterns (not shown) contained primarily tetragonal zirconium oxide and occasionally small amounts of monoclinic tungsten oxide. At higher calcination temperatures (>800°C), the amount of monoclinic tungsten oxide and monoclinic zirconium oxide increased. On average, the resulting surface areas were 100 m2, 100 m2, 150 m2, 200 m2, 300 m2, 400 m2, 500 m2, and 600 m2, respectively. 2 / g, NH 3 The uptake was 0.20 mmol / g.

[0108] Example 17: General Extrusion Conditions Self-bonding extrusion of powder samples was carried out in a 1" DIAMOND AMERICA extruder using 100g of powder that had been milled in a LANCASTER pulverizer for 5 minutes. Following the initial milling period, 10g of CAPLUBE® ethoxylated castor oil was added to the milled powder and milled for an additional 5 minutes. Sufficient water was then added to form a paste for extrusion of 1 / 16" quadruple lobes. After extrusion, the extrudates were dried at 120°C for several hours. The extrudates were mixed with NH 4 NO 3 After drying, the extrudates were calcined at 1000°F (537.7°C) for 4 hours to prepare the final extrudates. Typical crush strength for this type of extrudate was >50 lb / in.

[0109] Example 18: H 2 PtCl 6 to a target metal content of 0.5 wt.% using Water uptake was measured to determine the amount of water required for incipient wet impregnation of the metal salt onto the extrudates. 95%-98% of the water uptake was taken and subtracted from the amount of metal salt stock solution for dilution to determine the amount of water required to form a diluted metal salt solution for impregnation. 6.5 g of H2O diluted with 3.3 g of water was added to 50 g of extrudates. 2 PtCl 6 The extrudates were impregnated with a 3.8% Pt solution of 10 ...

[0110] Example 19: (NH 3 ) 4 Pt(NO 3 ) 2 to a target metal content of 0.5 wt.% using This example uses 7.9 g of 3.2% (NH 3 ) 4 Pt(NO 3 ) 2 The procedure was the same as in Example 18, except that 2.0 g of 1,2-dichlorophenyl ether was diluted with 2.0 g of water and used for metal impregnation. The dispersion of the metal on the extrudates ranged between 25% and 40%, as measured by CO chemisorption. The active form of the catalyst was prepared by reducing the extrudates under hydrogen at 180° C.-220° C. for 2-3 hours.

[0111] Table 1 summarizes various properties of the samples produced in Examples 1 to 12. Surface area is N 2 Determined by BET adsorption / desorption isotherms. NH 3 Incorporation was measured by temperature programmed adsorption / desorption and collidine incorporation was measured gravimetrically. Powder X-ray diffraction peaks were measured using CuKα radiation. The following approximate 2θ peak positions are characteristic: m-WO 3=24.4°, m-ZrO 2 = 28.4°, and tetragonal ZrO 2 (t-ZrO 2 )=30.2°.

[0112] [Table 1]

[0113] Table 2 summarizes the compositional profiles, including W surface density, of the samples produced in Examples 1 to 12. The tungsten (W) surface density is measured as (a) the W content (wt%) measured by X-ray fluorescence, and (b) the N 2 The surface area was calculated from the surface area measured by BET.

[0114] [Table 2]

[0115] 1 is a graph showing the powder XRD profiles and their corresponding surface areas of the samples produced in Examples 5 to 8. The powder XRD patterns showed the amount of monoclinic tungsten oxide and monoclinic zirconium oxide formed under different synthesis conditions.

[0116] 2A and 2B are graphs showing the powder XRD profiles and their corresponding surface areas of samples produced in Examples 1 and 5, respectively, at various stages of processing. The powder XRD patterns of both samples showed broad diffraction peaks of the uncalcined material (hydroxide), which may be related to the layered precursor before calcination. The layered precursor had a significantly higher surface area than the calcined product. Upon calcination at high temperatures, small tungsten oxide clusters and tetragonal zirconium oxide were formed.

[0117] 3 is a graph showing the powder XRD profiles of the mixed metal oxide of Example 5 calcined at three different temperatures. As the temperature was increased beyond a threshold value, monoclinic tungsten oxide species and monoclinic zirconium oxide species were formed, followed by a decrease in surface area, all of which reduced the activity of the catalyst.

[0118] Table 3 shows the effect of calcination temperature on various properties of the mixed metal oxides prepared in Example 5. Ammonia and collidine uptake values ​​(representing surface acidity) were measured prior to the formation of active catalyst. Figure 4 is a graph showing the distribution of surface acidity as a function of calcination temperature for the mixed metal oxides prepared in Example 5.

[0119] [Table 3]

[0120] Performance testing of some samples is shown below. Data was collected either in a high-throughput device (16-channel flow unit developed by hte GmbH High Throughput Experimental (HTE) company) or in a micro unit. All examples were extruded as self-bonding materials and impregnated with chloroplatinic acid targeting 0.5 wt% Pt, as described in Examples 17 and 18 unless otherwise specified.

[0121] Figure 5 shows the results of a test performed at 160°C, 200 psig, and H 2 1 is a graph of n-heptane conversion: cracking rate ratio as a function of cracking rate for the mixed metal oxide of Example 5 at a LHSV of 2:n-heptane ratio. A maximum cracking rate of about 9% was observed under various LHSV values. As shown, the n-heptane conversion: cracking rate ratio increased significantly at low cracking rates. At a cracking rate of about 5%, the ratio was about 13.

[0122] Tables 4-8 summarize the isomerization data obtained from the various samples prepared in the above examples and reacted under the conditions specified below.

[0123] Table 4 shows the results of the experiments performed at 170°C, 257 psig, 2 LHSV, and 2:1 H in the presence of various catalyst samples. 2 The reaction data obtained for the following ratios are summarized: -1 At an LHSV of 1000, 170°C and 250 psig, greater than 80% n-heptane conversion was achieved. Catalyst activation was performed as follows: the catalyst was quenched with 100 sccm N 2 Heat at 300 °C for 1 h under 100 sccm H 2 The mixture was heated at 220° C. under 350 psig for 3 hours. RON was determined as specified in Ghosh et al., Ind. Eng. Chem. Res., 2006, pp. 337-345, 45.

[0124] [Table 4]

[0125] Table 5 shows the results for 160°C, 207 psig, 4 LHSV, and 2:1 H 2 The reaction data obtained for the toluene:hydrocarbon ratios are summarized in Table 4. The catalysts were activated in the same manner as in Table 4.

[0126] [Table 5]

[0127] Table 6 shows the results for 160°C, 207 psig, 2LHSV, and H 2 Reaction data obtained with a 2:1 ratio of n-heptane to hydrocarbon is shown. Under these conditions, a conversion of more than 60% of n-heptane was achieved. The catalyst was activated in the same manner as in Table 4.

[0128] [Table 6]

[0129] Table 7 shows the reaction data for individual feeds of n-pentane, n-hexane, and n-heptane isomerized in the presence of samples prepared under various process conditions. The reaction data was obtained at 170° C., 188 psig, 3 WHSV, and H 2 The catalyst was activated with 100 sccm N2O, and the n-hexane was converted to 100 sccm N2O. Under these conditions, >25% of the n-pentane, >55% of the n-hexane, and >90% of the n-heptane in the feed mixture were converted. 2 Heat at 300 °C for 1 h under 100 sccm H 2 The mixture was heated under 350 psig at 220° C. for 24 hours.

[0130] [Table 7]

[0131] Table 8 shows the reaction data for individual feeds of n-pentane and n-hexane over the 750° C. calcined, precious metal-impregnated catalyst (Example 5) at various temperatures. The reaction data was obtained at 350 psig, 2 LHSV, and H 2 The catalyst was activated as follows: 100 sccm N 2 Heat at 300 °C for 1 h under 100 sccm H 2 Heated under 350 psig and 180° C. for 3 hours (micro units).

[0132] [Table 8]

[0133] All documents described herein, including priority documents and / or test procedures, to the extent not inconsistent with this text, are incorporated herein by reference for purposes of all jurisdictions where such practice is permitted. As is apparent from the general description and specific embodiments above, forms of the invention have been illustrated and described, but various modifications can be made without departing from the spirit and scope of the invention. Accordingly, it is not intended that the disclosure be limited thereby. For example, the compositions described herein may not include any component or composition not expressly described or disclosed herein. Any method may be devoid of a step not described or disclosed herein. Similarly, the term "comprising" is considered synonymous with the term "including." Whenever a method, composition, element, or group of elements is preceded by the transitional phrase "comprising," the same composition or group of elements may be described with the transitional phrase "consisting essentially of," "consisting of," "selected from the group of consisting of," or "is," which precedes the definition of the composition, element, or element, and vice versa.

[0134] One or more exemplary embodiments incorporating one or more elements of the present invention are presented herein. For clarity, not all features of a physical implementation are described or shown in this application. It is understood that the development of a physical embodiment incorporating one or more elements of the present disclosure requires making numerous implementation-specific decisions to achieve the developer's goals, such as compliance with system-related, business-related, government-related, and other constraints, which may vary from layer to layer or from time to time. While the developer's efforts may be time-consuming, such efforts are nevertheless routine for those of ordinary skill in the art having the benefit of this disclosure.

[0135] Unless otherwise indicated, all numbers used in this specification and the related claims expressing, for example, amounts of ingredients, properties such as molecular weights, reaction conditions, and the like, should be understood in all instances to be modified by the term "about". Accordingly, unless otherwise indicated, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending on the desired properties sought to be obtained by the embodiments of the present disclosure. At the very least, and without limiting the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be construed by applying ordinary rounding techniques in light of at least the number of reported significant digits.

[0136] Whenever a numerical range with a lower limit and an upper limit is disclosed, any numerical value and any range falling within that range is specifically disclosed, including the lower and upper limits. In particular, all ranges of values ​​(in the form "from about a to about b," or equivalently "from approximately a to b," or equivalently "from approximately a to b") disclosed herein, "a to b (ab)") should be understood to represent any numerical value and range falling within the broader range of values. In addition, terms in the claims have their plain and ordinary meaning unless expressly and unambiguously defined by the patentee. Furthermore, the indefinite article "a" or "an" used in the claims is defined herein to mean one or more elements that it introduces.

[0137] Thus, the present disclosure is well adapted to achieve the objects and advantages mentioned, as well as those inherent therein. The specific embodiments disclosed above are merely exemplary, and the disclosure may be modified and implemented in different but equivalent manners apparent to those skilled in the art having the benefit of the teachings herein. Moreover, no limitations are intended to the details of construction or design shown herein, except as set forth in the following claims. Thus, it is apparent that the specific exemplary embodiments disclosed above may be altered, combined or modified, and all such variations are deemed to be within the scope and spirit of the present disclosure. The embodiments illustratively disclosed herein may be suitably implemented in the absence of elements not specifically disclosed herein and / or any elements disclosed herein.

Claims

1. being at least partially crystalline and comprising a mixed metal oxide including tungsten, zirconium and a variable oxidation state metal; the variable oxidation state metal comprises a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof; the mixed metal oxide comprising 5 wt.% to 25 wt.% tungsten, 40 wt.% to 70 wt.% zirconium, and 0.01 wt.% to 5 wt.% variable oxidation state metals, each based on the total mass of the mixed metal oxide; The mixed metal oxide has a viscosity of 50 mm as measured according to ISO 9277. 2 / g or more and having a total surface area of: Ammonia uptake of 0.05-0.3 mmol / g as measured by temperature programmed adsorption / desorption, or Gravimetrically, collidine incorporation of 100 μmol / g or more The composition comprising at least one of the following:

2. 2. The composition of claim 1, wherein the mixed metal oxide is impregnated with a precious metal, the precious metal being present at 0.01% to 2% by weight based on the total weight of the mixed metal oxide and the precious metal.

3. The composition described in claim 2, wherein the precious metal comprises at least one precious metal selected from the group consisting of Pt, Pd, Rh, and any combination thereof.

4. 3. The composition of claim 2, wherein the mixed metal oxide, when activated, is effective to isomerize n-heptane at a conversion:cracking rate ratio of 10 or greater and a cracking rate of 10% or less.

5. The mixed metal oxide is 60m 2 / g ~ 130m 2 The composition of claim 1 or 2 having a total surface area in the range of 1 / g.

6. The mixed metal oxide has a W atom / nm2 content in the range of 2-20. 2 3. The composition of claim 1 or 2, having a tungsten surface density measured as:

7. The mixed metal oxide is monoclinic zirconium oxide (m-ZrO 2 ) to monoclinic tungsten oxide (m-WO 3 3. The composition according to claim 1, wherein the powder X-ray diffraction peak height ratio of

8. 3. The composition of claim 1 or 2, wherein the mixed metal oxide comprises 9 wt.% to 20 wt.% tungsten, 40 wt.% to 70 wt.% Zr, and 0.01 wt.% to 2 wt.% variable oxidation state metals, each based on the total mass of the mixed metal oxide.

9. 3. The composition of claim 1 or 2, wherein the variable oxidation state metal is selected from the group consisting of Fe, Mn, Cu, Ce, and any combination thereof.

10. The composition of claim 9, wherein the variable oxidation state metal comprises Fe.

11. 3. The composition of claim 1 or 2, further comprising a binder mixed with said mixed metal oxide.

12. A method for producing the composition of claim 1 or 2, comprising the steps of: combining in a reaction mixture under alkaline conditions having a pH of 7.5 or greater a zirconium source, a tungsten source, and a variable oxidation state metal source; obtaining a slurry comprising a co-precipitated reaction product formed from the zirconium source, the tungsten source, and the variable metallic state metal source under the alkaline conditions; digesting the slurry to form an amorphous digested product from the co-precipitation reaction product; calcining the amorphous digestion product in air at a temperature in the range of 700°C to 900°C; Consisting of The method of claim 1, wherein the variable oxidation state metal comprises a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof.

13. 13. The method of claim 12, wherein the reaction mixture is formed by combining a first solution comprising the tungsten source and a second solution comprising the zirconium source and the variable oxidation state metal source in an alkaline solution having a pH of 9-10.

14. The method of claim 12, wherein the mixed metal oxide is impregnated with a precious metal, the precious metal being present at 0.01% to 2% by weight based on the total weight of the mixed metal oxide and the precious metal.

15. The manufacturing method described in claim 14, wherein the precious metal comprises at least one precious metal selected from the group consisting of Pt, Pd, Rh, and any combination thereof.

16. further comprising introducing a precious metal precursor into said mixed metal oxide after calcination by incipient wetness impregnation, vacuum infiltration impregnation, or any combination thereof; Preferably, the noble metal precursor is (NH 3 ) 4 Pt(NO 3 ) 2 , (NH 3 ) 4 Pt(OH) 2 , (NH 3 ) 4 PtCl 2 , H 2 PtCl 6 , (NH 3 ) 2 H 2 PtCl 4 and any combination thereof.

17. The method of claim 16, wherein the precious metal precursor comprises a water-soluble metal complex selected from the group consisting of (NH3)4Pt(NO3)2, (NH3)4Pt(OH)2, (NH3)4PtCl2, H2PtCl6, (NH3)2H2PtCl4, and any combination thereof.

18. The method of claim 12 further comprising forming an extract from the mixed metal oxide.

19. 13. The method of claim 12, wherein the zirconium source is selected from zirconium salts, the tungsten source is selected from ammonium metatungstate, alkali metal metatungstate, tungsten chloride, tungstic acid, and combinations thereof, and the variable oxidation state metal source is selected from the corresponding water soluble metal salts.

20. heating the mixed metal oxide of claim 1 under hydrogen to form an activated catalyst; Under isomerization reaction conditions, at least one C 7+ contacting a hydrocarbon feedstock comprising normal alkanes with the activated catalyst; The at least one C 7+ forming one or more branched alkanes from the normal alkanes; Consisting of The method wherein the mixed metal oxide is further impregnated with 0.01% to 2% by weight of a precious metal, based on the total weight of the mixed metal oxide and the precious metal.

21. 21. The method of claim 20, wherein the activated catalyst is effective to isomerize n-heptane at a conversion:cracking rate ratio of 10 or greater, with a cracking rate of 10% or less.

22. The isomerization reaction conditions are as follows: Temperature in the range of 150°C to 210°C, a ratio of hydrogen to hydrocarbon feedstock ranging from 1:1 to 3:1; Pressures ranging from 150 psig to 350 psig; and 0.5h -1 ~6h -1 Liquid hourly space velocity in the range 22. The method of claim 20 or 21, comprising one or more of: